Development and early outcomes of the national training initiative for transanal total mesorectal excision in the UK. (22nd March 2020) - Francis, N.; Penna, M.; Carter, F.; Mortensen, N. J.; Hompes, R.; ,
Abstract: Aim: Transanal total mesorectal excision (TaTME) has attracted substantial interest amongst colorectal surgeons but its technical challenges may underlie the early reports of visceral injuries and oncological concerns. The aim of this study was to report on the feasibility, development and the outcome of the national pilot training initiative for TaTME‐UK. Methods: TaTME‐UK was successfully launched in September 2017 in partnership with the healthcare industry and endorsed by the Association of Coloproctology of Great Britain and Ireland. This multi‐modal training curriculum consisted of three phases: (i) set‐up; (ii) selection of pilot sites; and (iii) formal proctorship programme. Bespoke Global Assessment Scoring (GAS) forms were designed and completed by both trainees and mentors. Data were collected on patient demographics, tumour characteristics and perioperative clinical and histological outcomes. Results: Twenty‐four proctored cases were performed by 10 colorectal surgeons from five selected pilot sites. Median operative time was 331 ± 90 (195–610) min which was reduced to 283 ± 62 (195–340) min in the final case. Independent performance (GAS score of 5) was achieved for most operative steps by case 5. There was one conversion (4.2%), but no visceral injuries. Pathological data confirmed no bowel perforation and intact quality of the mesorectal TME specimens with clear distal margin in all cases and circumferential margins in 23/24 cases (96%). Conclusion: This exploratory study demonstrates acceptable early outcomes in a small cohort suggesting that a competency‐based multi‐modal training programme for TaTME can be feasible and safe to implement at a national level.